Unmanned aerial vehicle technology to assess the state of threatened biogenic formations: The vermetid reefs of mediterranean intertidal rocky coasts. (5th April 2021) - Donnarumma, Luigia; D'Argenio, Antonio; Sandulli, Roberto; Russo, Giovanni Fulvio; Chemello, Renato
Abstract: Vermetid bioconstructions are biogenic formations, built by sessile gastropod molluscs belonging to the family Vermetidae worldwide distributed, occurring in the intertidal and upper subtidal in the rocky shores. In the Mediterranean basin, they occur in complex and tridimensional structures that enhance the local biodiversity, allowing to qualify the structuring species as ecosystem engineers. Due to their ecological relevance and considerable extension along the coasts, we assessed their structural complexity using unmanned aerial vehicle (UAV) technology, as tool of littoral cartography analysis of these bioconstructions, and plaster hemispheres dissolution as a descriptor index of the water movement on them. We adopted an UAV to produce a very high spatial resolution map along 830m of rocky coast where these vermetid gastropods occur. Through an orthophoto with a GSD (Ground Sample Distance) of 1 cm, different complexity values of indentation degree (or roughness profiles) of the reef boundaries were detected, corroborating literature data carried out with traditional measurement techniques (e.g., tape measure). Our results indicate that the most complex zone of reef is the outer edge, facing the open sea, with a decreasing trend toward the inner edge. Concerning the experimental approach conducted using plaster hemispheres placed along the platform, it reveals that water movement is a structuring factor of the vermetid reef complexity along the rocky coast. Overall, the application of UAV technique allows an appropriate approach to analyze different zones of the vermetid reefs with a high-accuracy on a large spatial scale, greatly reducing sampling effort, and generating important implications for future monitoring and conservation programs. Highlights: UAV technology was applied on an extended rocky coast (830m) colonized by vermetids. The ortophotomosaic was used in order to vectorise the vermetid bioconstructions. The three indentation boundaries of reef highlight different structural complexity. The cross-reef water current differently affects the outer and inner reef margins. Large platforms (>4m) lead to a different water action on reef zones.